2018
DOI: 10.1016/j.toxicon.2018.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of peptidic and proteinaceous toxins from social Hymenoptera venoms

Abstract: Among venomous animals, Hymenoptera have been suggested as a rich source of natural toxins. Due to their broad ecological diversity, venom from Hymenoptera insects (bees, wasps and ants) have evolved differentially thus widening the types and biological functions of their components. To date, insect toxinology analysis have scarcely uncovered the complex composition of bee, wasp and ant venoms which include low molecular weight compounds, highly abundant peptides and proteins, including several allergens. In H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 248 publications
(339 reference statements)
0
46
0
1
Order By: Relevance
“…Compared with venoms from other insect groups, venoms of the Hymenoptera have been the subject of extensive study. Here, we provide a general overview and refer the reader to other works for more detailed information (Piek, 1986;Aili et al, 2014;Moreau and Asgari, 2015;Konno et al, 2016;Lee et al, 2016;Touchard et al, 2016a;dos Santos-Pinto et al, 2018). Venom use arose in Hymenoptera associated with parasitic oviposition.…”
Section: Hymenopteramentioning
confidence: 99%
“…Compared with venoms from other insect groups, venoms of the Hymenoptera have been the subject of extensive study. Here, we provide a general overview and refer the reader to other works for more detailed information (Piek, 1986;Aili et al, 2014;Moreau and Asgari, 2015;Konno et al, 2016;Lee et al, 2016;Touchard et al, 2016a;dos Santos-Pinto et al, 2018). Venom use arose in Hymenoptera associated with parasitic oviposition.…”
Section: Hymenopteramentioning
confidence: 99%
“…Firstly, we demonstrated that the Hymenoptera venom extracts, used as the antigenic source in the immunoblot procedures, present the major allergens typically found in their respective species [ 20 ]. Seven proteins were found with relevant reactivity to the patient’s sera: Hyaluronidase (45 kDa), PLA2 (16 kDa), Api m6 (8 kDa) in Apis mellifera venom extract, PLA1 (34 kDa) and Ag 5 (23 kDa) in Polybia paulista venom, and PLA1B (35 kDa) and Ag 5 (24 kDa) in Solenopsis invicta venom ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the analysis of hymenopteran venoms proteins showed that some allergens, such as the Hyaluronidase [ 17 ] and phospholipase A2 from Apis mellifera [ 18 ] and phospholipase A1 from Solenopsis invicta [ 19 ], present CCDs in their structure. It is also known that Polybia paulista allergenic proteins, phospholipase A1 and antigen 5 are glycosylated proteins, so they do not have CCD epitopes, such as antigen 5 from Solenopsis invicta [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many of their members, including ants, bees and wasps, use venom for predation, defence and communication. These venoms seem to be highly heterogeneous and structurally complex, with a wide range of bioactive constituents being reported including sugars, formic acid, biogenic amines, polyamines, alkaloids, and peptides [4,5]. Considering this immense chemical diversity and the high species richness of this order, hymenopterans can be considered a vast, yet understudied resource for the discovery of new biochemicals that complements venom from other, better studied species such as spiders, scorpions, snakes and cone snails.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this immense chemical diversity and the high species richness of this order, hymenopterans can be considered a vast, yet understudied resource for the discovery of new biochemicals that complements venom from other, better studied species such as spiders, scorpions, snakes and cone snails. A systematic analysis of the chemical and structural diversity within hymenopteran venoms does not exist [4,5]. However, the high diversity of ant species with diverse ecology and evolutionary history predicts enormous potential for the discovery of bioactive peptides with novel structural scaffolds and pharmacology with applications in medicine and agriculture [6,7].…”
Section: Introductionmentioning
confidence: 99%